A comparative evaluation of a commercially available kojic acid and arbutin-containing test product with a test regime in the treatment of hyperpigmentation - Joshi, Rajiv; Sen, Dyotona; Choudhary, Sanjay (International Journal of Research in Dermatology, 2024)
Background: The study compared the effectiveness of kojic acid and arbutin-containing lotion (alone) with arbutin-containing facewash and kojic acid and arbutin-containing lotion in the reduction of pigmentation. Methods: The study compared the test product (lotion) and the test regime (lotion + facewash) over a period of 45 days. In both test groups, a thin layer of advance body lotion was applied to the face, neck, and upper trunk. In the test regime group (TRG), these areas were washed with advance facewash before the lotion was applied. Both groups used sunscreen (with a sun protection factor of 50). The primary outcomes measured were (i) skin radiance and skin pigmentation, (ii) skin gloss, and (iii) skin hydration. The secondary outcomes measured were clinical evaluation and a subjective self-assessment for tolerance and perception of the product. Results: The study included 61 participants. The TRG showed a statistically significant increase in skin hydration (at 21 days) and skin gloss compared to the test product group (TPG) (at 21 and 45 days) (p<0.05). The majority of participants in both groups reported a visible reduction in pigmentation and improved facial glow and hydration as compared to baseline. No serious adverse effects were reported. Conclusions: The use of kojic acid and arbutin-containing lotion alone and arbutin-containing facewash with the lotion led to significant improvements in skin radiance, lightening, gloss, and hydration as compared to the baseline, with the TRG showing significantly better clinical results than the TPG in terms of skin hydration and gloss.